Effect of Gyrokinesis Exercise on Lower Extremity Edema, Balance Ability, and Fatigue in office Women Workers - Mi-Kyung Kim; Kyoung-Bin Min (Asian Society of Kinesiology, 2024)
OBJECTIVES This study aims to confirm the effect of Gyrokinesis exercise on lower extremity edema, balance ability, and fatigue in office women. METHODS Subjects were allocated to an exercise group (n=14) performing 60-minute Gyrokinesis sessions twice weekly for eight weeks, or a control group (n=13) wearing compression stockings during work hours. Evaluations included measuring calf and ankle circumferences for lower extremity edema, conducting single-leg stands with eyes closed and Y-balance tests for balance improvements, and administering the Fatigue Severity Scale (FSS) questionnaire to assess changes in fatigue. RESULTS First, significant reductions in ankle circumference and extracellular fluid ratio were observed in lower extremity edema. Second, while no interaction effects were found between dynamic and static balance abilities, the exercise group showed notable improvements. Third, the exercise group exhibited significant enhancements in fatigue levels. CONCLUSIONS Gyrokinesis exercise is effective in reducing lower extremity edema, improving balance ability, and reducing fatigue in office working women.